2014
DOI: 10.1111/jcmm.12418
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 promotes MYCN non‐amplified neuroblastoma cell survival via β‐catenin stabilization

Abstract: Amplification of MYCN is the most well-known prognostic marker of neuroblastoma risk classification, but still is only observed in 25% of cases. Recent evidence points to the cyclic adenosine monophosphate (cAMP) elevating ligand prostaglandin E2 (PGE2) and β-catenin as two novel players in neuroblastoma. Here, we aimed to define the potential role of PGE2 and cAMP and its potential interplay with β-catenin, both of which may converge on neuroblastoma cell behaviour. Gain and loss of β-catenin function, PGE2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 53 publications
1
14
1
Order By: Relevance
“…Intriguingly, our study revealed higher expression levels of FZD2, LRP6 and cyclin D1 in MYCN -amplified SK-N-DZ NB cells and tumors, while β-catenin (both total and active) and MYC were higher expressed in MYCN -unamplified SK-N-AS cells and tumors. In support of this, other studies reported upregulated β-catenin and β-catenin target genes in high-risk NB tumor tissue without MYCN amplification in comparison to high-risk MYCN -amplified tumor sections [15, 33]. Importantly, FZD2 blockade reduced β-catenin staining intensity in both NB xenografts.…”
Section: Discussionsupporting
confidence: 64%
“…Intriguingly, our study revealed higher expression levels of FZD2, LRP6 and cyclin D1 in MYCN -amplified SK-N-DZ NB cells and tumors, while β-catenin (both total and active) and MYC were higher expressed in MYCN -unamplified SK-N-AS cells and tumors. In support of this, other studies reported upregulated β-catenin and β-catenin target genes in high-risk NB tumor tissue without MYCN amplification in comparison to high-risk MYCN -amplified tumor sections [15, 33]. Importantly, FZD2 blockade reduced β-catenin staining intensity in both NB xenografts.…”
Section: Discussionsupporting
confidence: 64%
“…We and other have previously shown that PGE 2 , through activation of cyclic AMP, is responsible for activating β-catenin, thus making the Gαs-coupled EP 2 and EP 4 receptor the most likely candidates [14]. Here, we observed no effect of specific antagonism of the EP 4 receptor on PGE 2 -induced β-catenin-dependent transcription, whereas antagonism of the EP 2 receptor completely abolished the effect of PGE 2 .…”
Section: Discussioncontrasting
confidence: 44%
“…Earlier studies by us and others have indicated that PGE 2 activates β-catenin-dependent transcription via cyclic AMP [13, 14, 4852]. When we investigated expression of the cyclic AMP effector Epac, we observed increased expression of the Epac1 subtype by PGE 2 .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations